Reflectance spectroscopy characterization of space debris. Issue 10 (15th May 2017) - Vananti, A.; Schildknecht, T.; Krag, H.
Abstract: When characterizing the space debris environment one important point is the identification of the physical properties of the space debris objects. Reflectance spectroscopy is a possible technique to study the surface material of these objects with observations from the ground. In this work the results collected from spectroscopy observations of space debris in orbit are presented. The observations were performed at the 1-m ESA Space Debris Telescope (ESASDT) in Tenerife equipped with a spectrograph in the 450–960 nm wavelength range. A preliminary classification using three different categories purely based on the shape and appearance of the spectra was proposed. Two debris objects with high AMR could be successfully associated with materials analyzed in the laboratory. The results show that the two debris objects are probably pieces of Kapton MLI with 'gold' and 'silver' coating, respectively. Color indices were extracted from the spectroscopic measurements. For high AMR objects the colors seem to be consistent with the proposed classification in three categories. The B-R and R-I laboratory measurements of 'gold' and 'silver' MLI taken from the literature are comparable with the obtained results.